Evaluation of the Adhesion of Ultrananocrystalline Diamond Coatings on WC-Co Substrates. (2017) - Fraga, M.A.; Contin, A.; Vieira, J.; Barbosa, D.; Campos, R.; Corat, E.; Trava Airoldi, V.J.
Abstract: In order to improve the cutting performance and lifetime of WC-Co hard metal tools, the issues related to synthesis and adherence of micro- and nanocrystalline CVD diamond coatings on these tools has been frequently discussed in the literature. However, there are few studies focused on ultrananocrystalline diamond (UNCD) coatings. In this study, we report the results of the characterization of UNCD coatings with different thicknesses with the purpose of evaluating their adhesion to WC-9%Co substrates. The structure and morphology of the UNCD coatings as a function of their thicknesses were investigated by Raman spectroscopy, atomic force microscopy (AFM) and field emission gun scanning electron microscope (FEG-SEM) analysis. The UNCD coating-substrate adhesion was evaluated by means of indentation tests with a load of 1000N.